A methodological extension to human reliability analysis for cargo tank cleaning operation on board chemical tanker ships - Akyuz, Emre; Celik, Metin; Akyüz, Emre; Çelik, Metin (Elsevier BV, 2015)
This is an article that conducts an empirical human reliability analysis for tank cleaning process on-board chemical tanker ship to enhance safety and operational reliability in maritime industry, providing a methodological extension through the integration of the AHP technique into the HEART approach. The paper provides a methodological development on decision making and human factors via extending a new approach to weight the proportion of the effect for calculating error producing conditions through operations. The model demonstration illustrates that cleaning of residues from hazardous cargoes such as acetic acid has required performing various critical tasks supported with recovery solutions. This research also provides practical insights along with reliability monitoring in ship operational level.